7 - Towards the Institutionalization of Research Uptake Management in Sub-Saharan African Universities - Harber, Tomas; Grobbelaar, Sara S. (Journal of Higher Education in Africa, 2022)
This paper examines the process of research uptake institutionalization tak- ing place at universities in the African context. It explores the importance of the emerging concept of Research Uptake Management (RUM) and provides a rationale for why it is becoming increasingly relevant within the higher education sector, both inside and outside of Africa. In so doing, this paper proposes a conceptual framework for strengthening RUM capacity based on an in-depth analysis of primary source material. It unpacks exist- ing capacity development needs across a selection of African universities within the sub-Saharan region, and examines how universities in a nascent stage of developing RUM practices are approaching the institutionalization of research uptake.